Optimization Treatment of Palm Kernel Cake for the Production of Bioadhesive for Plywood - Cheng, Wan Hee*; Wong, Ling Shing*; Lee, Xin Wei (INTI International University, 2020)
The expansion of plywood composite as well as health issues from synthetic call for the search of an alternative economical and environmentally friendly wood adhesive. Currently, the most widely used wood adhesives are synthetic adhesives derived from petrochemical, which cause severe health problems and pollution. Bio-adhesives that derived from natural sources such as palm kernel cake might be one of the solutions to replace the synthetic adhesives. The objectives of this study is to determine the best ratio of palm kernel cake biomass to alkaline (NaOH) treatment. In this study, the palm kernel cake powder was hydrolysed using NaOH (20 %) and mixed with different ratios of biomass to volume of NaOH, which are 1:3, 1:4, 1:5, 1:6 and 1:7. The results showed that bio-adhesive treated with 20% NaOH in ratio 1:7 have the highest shearing strength (p˃0.05) which is 0.32 ± 0.020 MPa. The mixture of NaOH. Therefore, the result suggested that PKC is a potential biomass for bio-glue production with 20% NaOH treatment in 1:7 ratio